Let-7b, miR-29b, and miR-125b as Potential Biomarkers for Differentiating Canine Mammary Carcinoma Histological Types - Tiago Ferreira; Francisca Dias; Ângela Alves; Adelina Gama; João F. Mano; Paula A. Oliveira; Rui Medeiros (Animals)
Epigenetics is the study of changes in organisms that result from modifications in gene expression rather than alterations in the genetic code itself [...]